Uji Formulasi Bahan Pembawa Jamur Antagonis Gliocladium sp. Terhadap Penyakit Layu Fusarium (Fusarium oxysporum f.sp. cepae) Tanaman Bawang Merah (Allium ascalonicum L.) - Siska Luthfiah; Satriyo Restu Adhi; Lutfi Afifah (Universitas Respati Indonesia, 2026)
Fusarium wilt disease caused by the fungus Fusarium oxysporum is one of the main diseases affecting shallots and can cause losses of up to 50%. Gliocladium sp. has the potential to be used as a biological agent because it is able to control pathogens and suppress the development of fusarium wilt disease. This study aims to determine which carrier material is most effective in producing the highest spore density of Gliocladium sp. and its antagonistic ability in reducing the intensity of Fusarium wilt disease in red onions. The study was conducted experimentally using a completely randomised single-factor design to test the spore density of Gliocladium sp. on four types of carrier materials: U₁ (rice bran), U₂ (rice), U₃ (corn cobs), and U₄ (sorghum seeds) with six replications, and a single-factor Randomised Block Design to test Gliocladium sp. against Fusarium oxysporum wilt disease with seven treatments: G₀ (control), G₁ (fungicide), G₂ (Gliocladium sp. from rice bran), G₃ (Gliocladium sp. from rice), G₄ (Gliocladium sp. from corn kernels), G₅ (Gliocladium sp. from sorghum seeds), G₆ (commercial Gliocladium sp.), and four replications. The results of the study indicate that the use of various carrier materials significantly affects the spore density of Gliocladium sp. and in suppressing Fusarium wilt disease in red onions (Fusarium oxysporum f.sp. cepae). Treatment U₂ (rice) produced the highest spore density, 2.70 x1011 spores/ml. However, treatment G₃ (Gliocladium sp. on rice) yielded suboptimal results in terms of germination rate (20.0%) and disease severity (100%), thus failing to effectively suppress Fusarium wilt disease.